Hubungan Fathering dan Emotional Maturity dengan Intimacy dalam Menjalin Hubungan Romantis pada Mahasiswi - Sisy Tamara Hadisawa; Rr. Dini Diah Nurhadianti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This article aims to determine the relationship between fathering and emotional maturitywith intimacy in having a romantic relationship with female students at the Faculty ofPsychology, X University. The subjects in this study were 104 female students aged 18 to25 years in which the data collection method was using accidental sampling technique.Measuring instruments used were intimacy scale (14 items, α = 0.814), fathering scale (16items, α = 0.924), and emotional maturity scale (22 items, α = 0.760). Based on the resultsof data analysis using IBM SPSS Statistics 22 with bivariate correlation techniques, thereis a no significant relationship between fathering with intimacy in having a romanticrelationship of r = 0.090 and p = 0.362; (p) > 0.05, and there is a significant positiverelationship between emotional maturity with intimacy in having a romantic relationshipof r = 0.354 and p = 0.000; (p) < 0.05. Furthermore, the results of data analysis withmultivariate correlation techniques obtained correlation coefficient R = 0.361, R2 = 0.130,and p = 0.001; (p) < 0.05 . This states that there is a relationship between fathering andemotional maturity with intimacy in having a romantic relationship with female studentsat the Faculty of Psychology, X University